Proposal of a novel approach to the assessment of patient safety culture - Fourar, Youcef-Oussama; Benhassine, Wissal; Boubaker, Leila (Int. J. Behavioural and Healthcare Research, 2021)
The assessment of Patient Safety Culture (PSC) is often conducted using a quantitative approach based on questionnaires or a qualitative one focused on the deployment of Patient Safety Culture Maturity Models (PSCMM). These two approaches suffer from a number of limitations and their resolution is only possible by exploiting the possible complementarity that exists between them. Indeed, to overcome their inherent limits, it is imperative to merge the two PSC approaches in a single approach called quali-quantitative evaluation of PSC. This article fits into this context and aims to materialise the merger of PSC approaches through their co-deployment. This will make it possible to capitalise the scores of the HSOPSC dimensions in terms of PSC maturity levels.